Antibiotic Susceptibility Pattern of Shigella spp. Isolated from Patients Suspected of Acute Gastroenteritis - Basnet, Bishal; Niroula, Dhirendra; Acharya, Jyoti; Basnyat, Shaila (Journal of Institute of Science and Technology, 2021)
Shigellosis, an intestinal infection caused by Shigella species, is manifested by bloody diarrhea. Due to the surge in multidrug-resistant (MDR) Shigella species, the control of shigellosis has been a big challenge. This study aims to determine the prevalence and assess the antibiotic susceptibility pattern of Shigella species. During our study period of five months from April 2014 to August 2014 at Sukraraj Tropical and Infectious Disease Hospital, Teku, Kathmandu, a total of 653 stool samples were collected from the patients suspected of acute gastroenteritis. The standard microbiological procedure was followed for the isolation and identification of Shigella species. Assessment of antibiotic susceptibility pattern of the Shigella species was done by Kirby-Bauer disk diffusion method following CLSI guidelines. The study found 25(3.82%) cases were Shigella positive. Among them, 18(72%) were S. flexneri, 6(24%) were S. dysenteriae, and 1(4%) was S. sonnei. The patients in the age group 16-45 years were highly susceptible to infection as the higher proportion 16(64%) of Shigella species were isolated from this age group (p> 0.05). Shigella species were found to be highly susceptible to Cefotaxime (100%), a third-generation cephalosporin. Nalidixic acid, on the other hand, was the least effective antibiotic as 20(80%) of the Shigella isolates were resistant, followed by Ampicillin 18(72%), Cotrimoxazole 13(52%), and Ciprofloxacin 9(36%). A higher proportion of [10(40%)] of our study isolates were MDR. Our results show that Nalidixic acid, Ampicillin, Cotrimoxazole, Ciprofloxacin, and Ofloxacin cannot be used as empirical therapy for the treatment of Shigella infection as Shigella species were highly resistant to these antibiotics. So, for the MDR Shigella infection, we suggest third-generation cephalosporin as an option.